2019
DOI: 10.1186/s12870-019-1699-9
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of Fusarium root rot resistance QTL Fsp-Ps 2.1 of pea under controlled conditions

Abstract: BackgroundDry pea production has increased substantially in North America over the last few decades. With this expansion, significant yield losses have been attributed to an escalation in Fusarium root rots in pea fields. Among the most significant rot rotting pathogenic fungal species, Fusarium solani fsp. pisi (Fsp) is one of the main causal agents of root rot of pea. High levels of partial resistance to Fsp has been identified in plant genetic resources. Genetic resistance offers one of the best solutions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 44 publications
2
47
0
Order By: Relevance
“… Coyne et al (2019) reported a significant QTL ( Fsp-Ps2.1 ) that accounts for 44.4 to 53.4% of the phenotypic variance for resistance to Fsp and this QTL shows a confidence interval of 1.2 cM. Fsp-Ps2.1 was mapped within the interval of the pigmented flower/anthocyanin pigmentation gene called as gene A in that study.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“… Coyne et al (2019) reported a significant QTL ( Fsp-Ps2.1 ) that accounts for 44.4 to 53.4% of the phenotypic variance for resistance to Fsp and this QTL shows a confidence interval of 1.2 cM. Fsp-Ps2.1 was mapped within the interval of the pigmented flower/anthocyanin pigmentation gene called as gene A in that study.…”
Section: Discussionmentioning
confidence: 86%
“…This defensin was also found to colocalize with a major QTL (mpIII-4) involved in resistance to Mycosphaerella pinodes in pea (Prioul-Gervais et al, 2007). DRR230 gene does not co-localize with any of the major QTLs identified by Coyne et al (2019).…”
Section: Pathogenesis-related (Pr) Genesmentioning
confidence: 89%
See 2 more Smart Citations
“…A strong QTL, Fsp-Ps 2.1 , governing resistance to Fsp has been detected in the recombinant inbred line (RIL) populations of pea (Baccara × PI 180693). The QTL Fsp-Ps 2.1 has been identified along with two other minor variance QTLs using three criteria: root disease severity, ratios of diseased vs. healthy shoot heights, and dry plant weights under controlled conditions (Coyne et al, 2019).…”
Section: Using Genomics To Understand the Basics Of Plant–pathogen Inmentioning
confidence: 99%